2005
DOI: 10.1021/jm050542x
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory Chemistry toward the Identification of a New Class of Multidrug Resistance Reverters Inspired by Pervilleine and Verapamil Models

Abstract: On the basis of the present knowledge of the substrate recognition site of ABC transporter proteins and inspired by the structures of verapamil and pervilleine A, a new class of Pgp-mediated multidrug resistance (MDR) reverters has been designed and synthesized. The new compounds are flexible molecules carrying one or two basic nitrogen atoms flanked, at properly modulated distance, by two aromatic moieties. Most of the molecules studied possess MDR inhibitory activity on anthracycline-resistant erythroleukemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
76
2
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(87 citation statements)
references
References 58 publications
8
76
2
1
Order By: Relevance
“…4D, the effect of naringenin on the mRNA expression of MDR1, MRP1 and MRP2 in all four cell lines was not observed, and similar result was found for verapamil treatment. Previous studies have shown that verapamil can prevent the drug pump of Pgp by inhibiting its activity (32,33). Our results suggest that naringenin enhances the cellular accumulation of doxorubicin through modulating the function of MRPs but not their expression levels.…”
Section: Naringenin Has No Effect On Expression Of Mdr1 and Mrpsmentioning
confidence: 50%
See 1 more Smart Citation
“…4D, the effect of naringenin on the mRNA expression of MDR1, MRP1 and MRP2 in all four cell lines was not observed, and similar result was found for verapamil treatment. Previous studies have shown that verapamil can prevent the drug pump of Pgp by inhibiting its activity (32,33). Our results suggest that naringenin enhances the cellular accumulation of doxorubicin through modulating the function of MRPs but not their expression levels.…”
Section: Naringenin Has No Effect On Expression Of Mdr1 and Mrpsmentioning
confidence: 50%
“…Verapamil, a well known inhibitor of the P-glycoproteininduced MDR phenotype, has been used to modulate the activity of P-gp and to reverse the multidrug resistance (32,33). However, our study showed that verapamil was ineffective in increasing cytotoxicity of doxorubicin in the non-expressing P-glycoprotein cells such as A549 and MCF-7 cells (Fig.…”
Section: Discussionmentioning
confidence: 70%
“…Molecular flexibility was added as a further characteristic to allow the molecules to choose the most productive binding modes, within the large P-gp recognition site, which would result in a high affinity interaction. Actually, this approach provided good results since most of those compounds proved to be very potent MDR reversers [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…The third-generation of P-gp inhibitors such as tariquidar and zosuquidar have high potency and specificity, and are being tested in phase III clinical trials in conjunction with chemotherapy to determine whether P-gp inhibition can restore, enhance or prolong drug sensitivity (Longley et al, 2005). In addition to the P-gp inhibitors of third-generation, derivatives of verapamil with reduced cardiovascular activity are very promising (Teodori et al, 2005;Biscardi et al, 2006) in treatment of AML patients that achieved complete remission or presented a resistant disease. Finally, an inhibition of drug efflux might be most beneficial when combined with anticancer drug that specifically targets the stem cells, such as imatinib, which targets the leukaemia stem cells carrying the BCR-ABL fusion protein (Dean et al, 2005).…”
Section: Inhibition Of Atp-dependent Transportersmentioning
confidence: 99%